2016
DOI: 10.1007/s00423-016-1524-y
|View full text |Cite
|
Sign up to set email alerts
|

Rescue ALPPS is efficient and safe after failed portal vein occlusion in patients with colorectal liver metastases

Abstract: PurposeThe aim of this study was to investigate whether associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) can be used as an effective and safe rescue procedure in patients with colorectal liver metastases (CRLM) and insufficient effect on the future liver remnant (FLR) after previous portal vein occlusion (PVO).MethodsEleven patients with bilobar CRLM treated with neoadjuvant chemotherapy and previous PVO with insufficient effect on the FLR were analyzed retrospectively from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…It was observed that such a strategy was able to achieve a more rapid and robust hypertrophy of the FLR (107). Thus, the volume of the FLR increased to more than 30% of TLV in more than 90% of patients and this hypertrophy was achieved after 7-10 days following the first stage (101,107,108). These results led to an impressive higher resectability rate, exceeding 90% (89).…”
Section: Associating Liver Partition and Portal Vein Ligation For mentioning
confidence: 65%
See 1 more Smart Citation
“…It was observed that such a strategy was able to achieve a more rapid and robust hypertrophy of the FLR (107). Thus, the volume of the FLR increased to more than 30% of TLV in more than 90% of patients and this hypertrophy was achieved after 7-10 days following the first stage (101,107,108). These results led to an impressive higher resectability rate, exceeding 90% (89).…”
Section: Associating Liver Partition and Portal Vein Ligation For mentioning
confidence: 65%
“…This approach has been employed to overcome the disadvantages of the two previous strategies (101). This operation was performed until now almost exclusive in patients whose primary tumor has already been resected.…”
Section: Associating Liver Partition and Portal Vein Ligation For mentioning
confidence: 99%
“…Patients with previous PVO with an insufficient response to the procedure, i.e., still with a FLR/BW of < 0.5%, were also considered eligible for inclusion in the study if they fulfilled the inclusion criteria mentioned above. Some of our patients were also included in previously published studies, one in which liver volume and function in ALPPS were assessed with a multimodal approach [12] and another evaluating only rescue ALPPS patients after failed PVO [13]. …”
Section: Methodsmentioning
confidence: 99%
“…In the patients who previously underwent embolization or ligation of the portal vein, i.e., before ALPPS, these procedures were performed as described previously [13]. …”
Section: Methodsmentioning
confidence: 99%
“…This procedure has been reported for patients with insufficient FLR hypertrophy following PVE [47,48,49]. Mean FLR hypertrophy after sequential PVE and ALPPS ranges from 57 to 65% [48,49].…”
Section: Options To Improve Future Liver Remnant Hypertrophymentioning
confidence: 99%